The flavor asymmetry in the polarized proton sea - Steffens, F. M. [UNESP] (FapUNIFESP (SciELO), 2004)
We perform a careful study on the effect of the Pauli blocking to the light polarized antiquark structure of the proton sea. We develop the formal expressions for the polarized antiquark distributions, highlighting the role played by quark statistics and the vacuum structure. The ratio involving the polarized antiquarks is calculated. In particular, it is found that Δd̄(x)/Δū(x) should be negative and x independent.